12x+6y=12

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Subtract 12x from both sides of the equation.

6y=12-12x

Divide each term by 6 and simplify.

Divide each term in 6y=12-12x by 6.

6y6=126+-12×6

Cancel the common factor of 6.

Cancel the common factor.

6y6=126+-12×6

Divide y by 1.

y=126+-12×6

y=126+-12×6

Simplify 126+-12×6.

Simplify each term.

Divide 12 by 6.

y=2+-12×6

Cancel the common factor of -12 and 6.

Factor 6 out of -12x.

y=2+6(-2x)6

Cancel the common factors.

Factor 6 out of 6.

y=2+6(-2x)6(1)

Cancel the common factor.

y=2+6(-2x)6⋅1

Rewrite the expression.

y=2+-2×1

Divide -2x by 1.

y=2-2x

y=2-2x

y=2-2x

y=2-2x

Reorder 2 and -2x.

y=-2x+2

y=-2x+2

y=-2x+2

y=-2x+2

Using the slope-intercept form, the y-intercept is 2.

b=2

Find the Y-Intercept 12x+6y=12